The Research into Dark Mode: A Systematic Review Using Two-Stage Approach and S-O-R Framework - Aiyi Yang; Chuhiang GOH; Limjing YI (International Journal of Computational and Experimental Science and Engineering, 2025)
Many company owners are taking notice of the popularity of dark mode in mobile apps, and many users are opting to utilize it for various reasons. There haven't been many comprehensive studies on the idea of dark mode or its definition, therefore it is still a relatively new area of study in academia. To add insult to injury, academic conclusions on ongoing investigations and forthcoming developments in the dark mode are few. Many people still disagree on the benefits and drawbacks of dark mode. To fill this void, this paper reviewed the literature on dark mode from a variety of academic fields. Its goal was to lay the groundwork for future research on the topic of dark mode and user experience by developing a basic research methodology for studying the two together. This report used a two-step process based on the Scopus database to search for and gather papers about dark mode research over the last 30 years. After reviewing all of the papers, 35 met the inclusion and exclusion criteria. Dark mode's topics, background, theoretical underpinnings, and research methodologies were first examined in this work. Then, using the "Stimulus-Organism-Response (S-O-R)" paradigm, it categorized and combined the dark mode study variables. In the end, it suggested a study methodology that would explain the deeper meaning of dark mode and the connection between user behavior, their experience, and many variables. This work went above and above by outlining possible avenues for future dark mode research and pointing out where present document studies are lacking.